The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/jobm.202000575
|View full text |Cite
|
Sign up to set email alerts
|

Microbial, environmental and anthropogenic factors influencing the indoor microbiome of the built environment

Abstract: A built environment is a human‐made environment providing surroundings for human occupancy, activities, and settlement. It is supposed to safeguard humans from all undesirable and harmful pollutants; however, indoor concentrations of some pollutants are much greater than that of the outdoors. Bioaerosols infiltrate from the outdoors in addition to many indoor sources of bioaerosols including the use of various chemicals as well as activities like cooking, smoking, cleaning, or even normal movement. They are al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 151 publications
1
53
0
1
Order By: Relevance
“…However, some other significant and relevant factors are necessary to profile the total microbiome of an environment. For example, human activities, lifestyles and ventilation might have an extraordinary role in the making of these microbiome profiles 44 . A Comparison of β-diversity of bacterial compositions between sample types according to UniFrac distances.…”
Section: Resultsmentioning
confidence: 99%
“…However, some other significant and relevant factors are necessary to profile the total microbiome of an environment. For example, human activities, lifestyles and ventilation might have an extraordinary role in the making of these microbiome profiles 44 . A Comparison of β-diversity of bacterial compositions between sample types according to UniFrac distances.…”
Section: Resultsmentioning
confidence: 99%
“…Our results agree with previous studies that major sources of micro-contaminants attributed by humans' activities and human occupancy in residential areas [ 26 - 28 ]. Similarly, some other studies also reported that the nature of human contact and human behavior has great influence on in door environment [ 29 , 30 ] for instance, presence of bacteria in the kitchen surface area is influenced by the various kind of food [ 31 ], and surfaces area most often affected by hands containing higher concentrations of skin flora [ 32 ]. In commercial or social settings, bacteria of outdoor origin may be a more significant source for surfaces, although normal skin flora or microbes are also present in high concentration [ 33 ].…”
Section: Discussionmentioning
confidence: 97%
“…The composition of the microbiota also depends on the host’s genetics, diet, and cultural and geographical factors, which make it even more difficult to identify an ideal, universal profile of the healthy microbiome ( 8 , 9 ). Furthermore, lifestyle can significantly influence the microbial community; consequently, different microbiomes and microbiota are present in healthy rural and urban people ( 10 13 ). Due to this high variability, no conclusions should be drawn about the healthy microbiome and microbiota composition based on taxonomic classification, and as a result, more useful data could be provided by the metabolic functions ( 14 16 ).…”
Section: Intestinal Permeability and The Microbiomementioning
confidence: 99%